Revisioning Clinical Psychology: Integrating Cultural Psychology into Clinical Research and Practice with Portuguese Immigrants - James, Susan; Harris, Sara; Foster, Gary; Clarke, Juanne; Gadermann, Anne; Morrison, Marie; Bezanson, Birdie J. (Frontiers in Psychology, 2013)
This article outlines a model for conducting psychotherapy with people of diverse cultural backgrounds. The theoretical foundation for the model is based on clinical and cultural psychology. Cultural psychology integrates psychology and anthropology in order to provide a complex understanding of both culture and the individual within his or her cultural context. The model proposed in this article is also based on our clinical experience and mixed method research with the Portuguese community. The model demonstrates its value with ethnic minority clients by situating the clients within the context of their multi-layered social reality. The individual, familial, socio-cultural and religio-moral domains are explored in two research projects, revealing the interrelation of these levels/contexts. The article is structured according to these domains. Study 1 is a quantitative study that validates the Agonias Questionnaire in Ontario. The results of this study are used to illustrate the individual domain of our proposed model. Study 2 is an ethnography conducted in the Azorean Islands, and the results of this study are integrated to illustrate the other three levels of the model, namely family, sociocultural, and the religio-moral levels.